Thanks! : how the new science of gratitude can make you happier - Emmons, Robert A. (Houghton Mifflin Co., 2007)
Editor-in-chief of the Journal of Positive Psychology Dr. Robert Emmons draws on the first major scientific study of the subject to show how the systematic cultivation of gratitude can measurably change people's lives. People who regularly practice grateful thinking can increase their "set point" for happiness by as much as 25 percent. These increases can be sustained over a period of months--challenging the previously held notion that our set points for happiness are frozen at birth. Maintaining a gratitude journal for as little as three weeks results in better sleep and more energy. Emmons also reaches beyond science to bolster the case for gratitude by weaving in the writings of philosophers, novelists, and theologians. This book inspires readers to embrace gratitude and all the benefits it can bring into our lives.--From publisher description.